2018
DOI: 10.1016/j.jhep.2017.10.019
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of alcohol use disorder to decompensated cirrhosis among people with hepatitis C: An international study

Abstract: The burden of liver disease has been rising among people with hepatitis C globally. The recent introduction of highly effective medicines against hepatitis C (called direct-acting antivirals or DAAs) has brought renewed optimism to the sector. DAA scale-up could eliminate hepatitis C as a public health threat in the coming decades. However, our findings show heavy alcohol use is a major risk factor for liver disease among people with hepatitis C. If continued, heavy alcohol use could compromise the benefits of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 30 publications
0
59
0
4
Order By: Relevance
“…In a recent multicenter study, among patients with HCV diagnosis, the incidence of decompensated cirrhosis was higher among patients with alcohol use disorder. (20) Two additional smaller studies also found that alcohol in the presence of HCV and HBV cirrhosis, respectively, increases the risk of HCC. (21,22) We therefore add to the growing international literature that alcohol use may have more severe effects in subgroups of patients, including those who do not respond to treatment or have more advanced liver disease prior to therapy.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent multicenter study, among patients with HCV diagnosis, the incidence of decompensated cirrhosis was higher among patients with alcohol use disorder. (20) Two additional smaller studies also found that alcohol in the presence of HCV and HBV cirrhosis, respectively, increases the risk of HCC. (21,22) We therefore add to the growing international literature that alcohol use may have more severe effects in subgroups of patients, including those who do not respond to treatment or have more advanced liver disease prior to therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Accurate assessment of the full spectrum of ALD prevalence is challenging, particularly given the difficulty with identifying earlier, asymptomatic stages of ALD, such as ASH or moderate AH, challenges that may be overcome with broader use of noninvasive steatosis and fibrosis assessment tools and increased awareness for the need to diagnose early‐stage disease. Many studies underestimate the true prevalence and burden by counting as ALD only those patients without additional liver diseases such as HCV, in spite of the fact that concomitant ALD rates are as high as 61% in some patients with other liver diseases, in particular nonalcoholic steatohepatitis (NASH), HCV, and hemochromatosis . These factors may result in as much as a 2‐fold underestimate for ALD‐related mortality …”
Section: Prevalence and Burden Of Alcohol‐associated Liver Diseasementioning
confidence: 99%
“…Many studies underestimate the true prevalence and burden by counting as ALD only those patients without additional liver diseases such as HCV, in spite of the fact that concomitant ALD rates are as high as 61% in some patients with other liver diseases, in particular nonalcoholic steatohepatitis (NASH), HCV, and hemochromatosis. (14,19) These factors may result in as much as a 2-fold underestimate for ALD-related mortality. (11)…”
Section: Prevalence and Burden Of Alcohol-associated Liver Diseasementioning
confidence: 99%
“…For opioid‐associated diagnosis codes, the corresponding figures were 42.9% and 12.7%. Thus, while DAAs may eliminate HCV infection, other risk factors, such as alcohol misuse and obesity, could continue to drive liver disease progression and offset the beneficial impact of DAAs on ESLD and HCC burden . A history of alcohol abuse is associated with a high incidence of ESLD, regardless of whether patients are chronically infected with HCV or have cleared their infection and nonalcoholic fatty liver disease prevalence is increasing globally .…”
Section: Discussionmentioning
confidence: 99%